TINGKAT PENERAPAN BIOSEKURITI PADA PETERNAKAN AYAM PEDAGING KEMITRAAN DI KABUPATEN TABANAN DAN GIANYAR - Widyantara, Putu Riski Ananta; Wiyana, I K. A.; Sarini, N. P. (Jurnal Peternakan Tropika; Volume 1 No. 1 Tahun 2013)
The study is titled implementation of biosecurity on broiler farms in partnership Tabanan and Gianyar regency. The research was conducted in the village and the village of Tabanan district Selanbawak  and  Petak Kaja village of Gianyar district which lasted for three months from the month of February until April 2012. The study site selection using the "purposive", and the determination of respondents defined by the census method is a way of making the response and by taking all populations (Singarimbun and Effendi, 1989). Respondents of the study amounted to 49 farmers who are all broiler breeder two villages in both districts. This study aims to determine the level of implementation of biosecurity on broiler farms in partnership Tabanan and Gianyar.  The data used in this study is primary data obtained directly in the field and using secondary data is the result of the project the Australian Center for International Agricultural Research (ACIAR) Ah/2006/169 on a cheap and effective biosecurity for broiler breeders in sector 3 Indonesia ( commercial farms that implement biosecurity very simple). The measurement variables using scores from the data obtained. Data processing and analysis using descriptive statistics. Each of these respondents were grouped into five categories da were scored. This score is expressed in whole numbers 1,2,3,4, and 5 for each answer. The values ??are then grouped into 3 sections in accordance with the implementation of bio-security in Pre Entry, Point of Entry, and Post Entry is then the value in each group was summed and averaged and then analyzed using SPSS 16 with Independent Sample Test. These results indicate that the level of implementation of biosecurity on broiler farms in partnership Selanbawak Village Tabanan better at Pre Entry (P<0.05), than in the Village Petak Kaja Gianyar regency. While at Point of Entry and Post Entry at the both of District
Keywords: Biosecurity, Broiler farm, Partnership